Immune checkpoint inhibitors: an emerging cause of insulin-dependent diabetes. Issue 1 (13th February 2019) - Kotwal, Anupam; Haddox, Candace; Block, Matthew; Kudva, Yogish C
Abstract : Objective: Insulin-dependent diabetes can occur with immune checkpoint inhibitor (ICI) therapy. We aimed to characterize the frequency, natural history and potential predictors of ICI-induced diabetes. Research design and methods: We reviewed 1444 patients treated with ICIs over 6 years at our cancer center, and from the 1163 patients who received programmed cell death protein 1 (PD-1) inhibitors, we identified 21 such cases, 12 of which developed new-onset insulin-dependent diabetes and 9 experienced worsening of pre-existing type 2 diabetes. Results: ICI-induced diabetes occurred most frequently with pembrolizumab (2.2%) compared with nivolumab (1%) and ipilimumab (0%). The median age was 61 years, and body mass index was 31 kg/m 2, which are both higher than expected for spontaneous type 1 diabetes. Other immune-related adverse events occurred in 62%, the most common being immune mediated thyroid disease. New-onset insulin-dependent diabetes developed after a median of four cycles or 5 months; 67% presented with diabetic ketoacidosis and 83% with low or undetectable C-peptide. Autoantibodies were elevated in 5/7 (71%) at the time of new-onset diabetes. Diabetes did not resolve during a median follow-up of 1 year. Conclusions: PD-1 inhibitors can lead to insulin deficiency presenting as new-onset diabetes or worsening of pre-existing type 2 diabetes, with a frequency of 1.8 %. The underlying mechanism appears similar to spontaneous type 1 diabetes but there is a faster progression to severe insulin deficiency. Better characterization of ICI-induced diabetes will improve patient care and enhance our understanding of immune-mediated diabetes.